Comparative pharmacokinetics and safety evaluation of high dosage regimens of Andrographis paniculata aqueous extract after single and multiple oral administration in healthy participants - Songvut, Phanit; Rangkadilok, Nuchanart; Pholphana, Nanthanit; Suriyo, Tawit; Panomvana, Duangchit; Puranajoti, Porranee; Akanimanee, Jaratluck; Satayavivad, Jutamaad (Frontiers in Pharmacology, 2023)
The prolonged situation of the COVID-19 pandemic, with the emergence of new variants of SARS-CoV-2, not only imposes a financial burden on healthcare supports but also contributes to the issue of medication shortages, particularly in countries with limited access to medical resources or developing countries. To provide an alternative therapeutic approach during this crisis, there is an increasing research that has investigated the potential uses of Andrographis paniculata in supporting the application of herbal medicine for COVID-19.Purpose: This study aimed to investigate the safety profiles and clinical pharmacokinetics, specifically focusing on dose proportionality of the four major active diterpenoids of A. paniculata aqueous extract following oral administration of two different high doses of andrographolide.The participants received the aqueous extract capsules equivalent to 60 and 120 mg of andrographolide; and as multiple doses administered three times daily, calculated as 180 and 360 mg/day of andrographolide. Safety evaluation was assessed following the oral administration of the multiple doses. Abbreviations AUC, Area under plasma concentration-time curve ALT, alanine aminotransferase AST, aspartate aminotransferase BMI, Body mass index Cl/F, Apparent total clearance of the test substance removed from plasma after oral administration Cmax, Maximum plasma concentration CV, Coefficient of variation ESI, Electrospray ionization F, Absolute oral bioavailability GLP, Good laboratory practice GMP, Good manufacturing practice HPLC-DAD, High performance liquid chromatography with photodiode array detection HPLC-MS/MS, High performance liquid chromatography tandem mass spectrometry ICH-GCP, International conference on harmonization -good clinical practice IQR, Interquartile range IRB, Institutional review board IS, Internal standard Kel, Elimination rate constant MRM, Multiple reaction monitoring PVDF, Polyvinylidene difluoride membrane filter SD, Standard deviation SGOT, Glutamic-oxalacetic transaminase SGPT, Glutamic-pyruvic transaminase THP, Thai Herbal Pharmacopoeia Tmax, Time to reach maximum plasma concentration t1/2, Elimination half-life URTIs, Uncomplicated upper respiratory tract infections Vd/F, Apparent volume of distribution after non-intravenous administration WHO-ICTRP, WHO international clinical trials registry platform